Catharsis in Chinua Achebe’s Things Fall Apart - Ali, Dlnya Abdalla Mohammed Ali (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Catharsis in literature refers to the point at which the tension that has been built within the reader in the course of reading a work of literature gets released. The novel Things Fall Apart (1958) by Chinua Achebe focuses on a young Nigerian man of great fame who cannot be subject to domination by the white man. As a result, the story is characterized by a series of tense moments when the reader’s suspense builds to the brim. Nevertheless, catharsis comes at different points, starting with when Okonkwo can win the wrestling fight against Amalinze the Cat. Beginning with this victory, the reader gets to release tension at various times throughout the story, such as when Okonkwo becomes repentant of his mistakes and pays the fine to the earth goddess, when Ikernefuna arrives in Umuofia, and finally when Okonkwo commits suicide to seal his tragic fate. This analytical discussion of Things Fall Apart aims at identifying the critical points within the story when catharsis occurs, allowing the reader to release the inwardly built-up emotions at different points in the story.